Difusivitas Air pada Wortel selama Penggorengan Hampa Udara - Sutarsi Sutarsi; Budi Rahardjo; Pudji Hastuti (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2009)
Knowledge of moisture diffusivity was important for water loss modelling during deep fat vacuum frying. The appropri- ateness of model depended on the accuracy of moisture diffusivity value. The objective of this research was to calculate carrot moisture diffusivity during deep fat vacuum frying. Moisture diffusivity was obtained from rate of water loss multiplied by L2/π2. The rate of water loss was determined from unsteady-state diffusion equation. The slope of the time vs. dimensionless concentration ratio plot was the rate of water loss. Carrot was used as a sample in this research. The rate of water loss was determined during deep fat vacuum frying with variation of absolute pressure, temperature and initial moisture content. The result showed that moisture diffusivity depended on absolute pressure, temperature and initial moisture content. The result indicated that an increase in the temperature of frying and initial moisture content caused an increase in moisture diffusivity. While an increase in the absolute pressure induced decreasing of moisture diffusivity. The moisture diffusivities were accurately predicted at absolute pressure range from 20 – 40 kPa, initial moisture content range from 198 % (db) to 940 % (db) and temperature range from 80 to 110 oC.ABSTRAKPengetahuan mengenai difusivitas air sangat penting untuk pemodelan kehilangan air selama penggorengan hampa udara. Kesesuaian model tergantung atas akurasi nilai difusivitas air. Tujuan penelitian ini adalah untuk menghitung difusivitas air sebagai fungsi tekanan absolut, suhu dan kadar air awal bahan selama penggorengan hampa udara. Difusivitas air diperoleh dari laju kehilangan air dikalikan L2/π2. Laju kehilangan air ditentukan dari persamaan di- fusi tak mantap. Kemiringan dari kurva lama penggorengan terhadap rasio konsentrasi merupakan laju kehilangan air. Penilitian ini menggunakan wortel sebagai sampel. Laju kehilangan air ditentukan selama penggorengan hampa udara dengan variasi tekanan absolut, suhu dan kadar air awal bahan. Hasil penelitian menunjukkan bahwa difusivi- tas air tergantung atas tekanan absolut, suhu dan kadar air awal. Peningkatan suhu dan kadar air awal menyebabkan peningkatan difusivitas air. Sedangkan peningkatan tekanan absolut menyebabkan penurunan nilai difusivitas air. Difusivitas air diprediksikan secara tepat pada range tekanan absolut 20 - 40 kPa, suhu 80 - 110 oC dan kadar air awal 198 - 940 % (bk).